Analisis Kebutuhan Pengembangan Instrumen Penilaian Kepemimpinan Kepala Sekolah Melalui Supervisi Akademik Bagi Guru Sd Berbasis Random Wheel - Subadri, Subadri; Lestari, Wahyu; Setiawan, Deni; Sholeh, Muh. (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This study aims to analyze the need for the development of a principal leadership assessment instrument in the implementation of academic supervision based on interactive media Wordwall Random Wheel. The background of this research is based on the still dominant use of administrative and one-way supervision instruments in elementary schools, as well as the lack of involvement of teachers in providing feedback on the principal's leadership style. The research uses a qualitative approach with Research and Development (R&D) methods, adapting the 4D model (Define, Design, Develop, Disseminate). Data was obtained through observations, interviews, and questionnaires conducted in three elementary schools: SDN Bentarsari 01, SDN Bentarsari 02, and SDN Ciputih 01. The results of the study show that teachers need interactive, reflective, and collaborative instruments. The Random Wheel wordwall is considered effective in increasing teacher involvement in the supervision process, encouraging honest reflection, and building constructive two-way communication between teachers and principals. The implementation of this media has proven to be able to strengthen the role of school principals as professional coaches and not just administrative assessors.